PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN DAN NILAI PASAR PERUSAHAAN DI INDONESIA - Muhammad Halim Mukti Raharja; Agus Purwanto (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of intellectual capital and its components on financial performance as measured by the ratio of return on assets (ROA) and the company's market value is measured by the ratio q (Tobin'sQ). The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 - 2019. The sampling technique used in this study is purposive sampling technique, namely sampling with several criteria. The number of samples that met the sampling criteria in this study were 134 manufacturing companies (402 sample data). The results of this study indicate that intellectual capital has a positive influence on the Company's financial performance and market value. For each component, physical capital has a positive influence on the company's financial performance and market value. Human capital has a positive influence on financial performance, but has a negative effect on the company's market value. Relational capital is only able to explain its positive influence on the company's market value. In structural capital, it cannot explain the significant results.